The Use of a Rubric as a Tool to Guide Pre-Service Teachers in the Development of IEPs - Rosas, Clarissa E.; Winterman, Kathleen G. (Journal of the American Academy of Special Education Professionals, 2012)
The challenge of developing Individualized Education Program documents that are representative of a team decision making process and are in compliance with IDEA 2004 is well documented in the literature. One of the main objectives of IEPs is to serve as the foundation of a child’s academic program. Inclusion of children with disabilities in the general curriculum requires active involvement of all members of the child’s educational team. In an effort to instruct pre-service teachers in the development of compliant IEPs, this study investigated the use of an IEP Rubric to assist teacher candidates in the development of compliant IEPs. Results of the study indicate that the use of an IEP Rubric shows promise as an instructional tool to help in the preparation of preservice teachers.